A density functional study on the pKa of small polyprotic molecules. Issue 17 (19th February 2014) - Baba, Takeshi; Matsui, Toru; Kamiya, Katsumasa; Nakano, Masayoshi; Shigeta, Yasuteru; Brändas, Erkki; Szabados, Ágnes; Surján, Péter
<x xml:space="preserve">Abstract</x> The pKa values of several biologically important small molecules in aqueous solution, such as salicylic acid, histamine, and dopamine, were determined by density functional theory combined with the polarizable continuum model, which has been proposed for predicting pKa values of nucleic acids and proteins. These molecules have plural protonation sites and the inherent pKa determines which protons exist at a specific pH. Taking into account the ensemble average, and that the order of the deprotonation steps is specific among several possible pathways, it emerged that the calculated pKa values mostly reproduced the experimental ones within an error of ± 1.0 pKa units. © 2014 Wiley Periodicals, Inc.